A behavior change program to increase outings delivered during therapy to stroke survivors by community rehabilitation teams: The Out-and-About trial. Issue 4 (June 2016) - McCluskey, Annie; Ada, Louise; Kelly, Patrick J; Middleton, Sandy; Goodall, Stephen; Grimshaw, Jeremy M; Logan, Pip; Longworth, Mark; Karageorge, Aspasia
Background: Australian guidelines recommend that outdoor mobility be addressed to increase participation after stroke. Aim: To investigate the efficacy of the Out-and-About program at increasing outings delivered during therapy by community teams, and outings taken by stroke survivors in real life. Method: Cluster-randomized trial involving 22 community teams providing stroke rehabilitation. Experimental teams received the Out-and-About program (a behavior change program comprising a training workshop with barrier identification and booster session, printed educational materials, audit, and feedback). Control teams received printed clinical guidelines only. The primary outcome was the percentage of stroke survivors receiving four or more outings during therapy. Secondary outcomes included the number of outings received by stroke survivors during therapy and undertaken in real life. Results: At 12 months after implementation of the behavior change program, 9% of audited experimental group stroke survivors received four or more outings during therapy compared with 5% in the control group (adjusted risk difference 4%, 95% CI − 9 to 17, p  = 0.54). They received 1.1 (SD 0.9) outings during therapy compared with 0.6 (SD 1.0) in the control group (adjusted mean difference 0.5, 95% CI − 0.4 to 1.4; p  = 0.26). After six months of rehabilitation, observed experimental group stroke survivors took 9.0 (SD 3.0) outings per week in real life compared with 7.4 (SD 4.0) in the control group (adjusted mean difference 0.5, 95% CI − 1.8 to 2.8; p  = 0.63). Conclusion: The Out-and-About program did not change team or stroke survivor behavior.